PANDANGAN MASYARAKAT TERHADAP PELAKSANAAN PROGRAM KELUARGA BERENCANA (KB) DALAM MEWUJUDKAN KELUARGA SAKINAH DI KECAMATAN LEMBOR SELATAN - Nawang Sari, Rahma Pramudya; Rosalina Naitboho, Yanti; Hariyati, Hikmah; M. Sali, Jakaria; Idris. PS, Syarif (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2024)
Awareness of the importance of creating a sakinah family is the ideal that every married couple hopes for. There are a lot of efforts that must be made by all families to make this happen. The Ministry of Religion, through the Advisory Body for the Development and Preservation of Marriage (BP4) tries to provide an idea regarding efforts to form a sakinah family, namely by providing four main efforts that must be made. One of them is the implementation of the family planning (KB) program. The method used is a qualitative descriptive method with interview data collection techniques and documentation. Based on the conclusions in this research, the implementation of family planning in Golojong village, Nangalili Village, South Lembor District, West Manggarai Regency, is largely possible to create a sakinah family. Because they can maintain birth spacing, have an adequate economy, can save money, and married couples understand and love each other and always carry out the obligations commanded by Allah SWT. So that the family is more harmonious, safe, peaceful and peaceful in the family.